1992
DOI: 10.1126/science.1736364
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic Experience Alters Phonetic Perception in Infants by 6 Months of Age

Abstract: Linguistic experience affects phonetic perception. However, the critical period during which experience affects perception and the mechanism responsible for these effects are unknown. This study of 6-month-old infants from two countries, the United States and Sweden, shows that exposure to a specific language in the first half year of life alters infants' phonetic perception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

42
1,026
6
21

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,653 publications
(1,095 citation statements)
references
References 13 publications
42
1,026
6
21
Order By: Relevance
“…Our data more generally indicate that once children acquire the semantic system of their own language, their nonlinguistic sensitivity to those distinctions not made in their language diminishes over time. There appear to be similarities between the loss in sensitivity to tight versus loose fitting aspects of containment by English speakers shown in Experiment 2 and the loss of phonetic contrasts that are not phonemic in oneÕs native tongue (Kuhl, Williams, Lacerda, Stevens, & Lindblom, 1992;Werker & Lalonde, 1988). But there are many differences between the perceptual tuning of the sounds of oneÕs language and the conceptual tuning of semantic categories that result from what the language emphasizes.…”
Section: Discussionmentioning
confidence: 79%
“…Our data more generally indicate that once children acquire the semantic system of their own language, their nonlinguistic sensitivity to those distinctions not made in their language diminishes over time. There appear to be similarities between the loss in sensitivity to tight versus loose fitting aspects of containment by English speakers shown in Experiment 2 and the loss of phonetic contrasts that are not phonemic in oneÕs native tongue (Kuhl, Williams, Lacerda, Stevens, & Lindblom, 1992;Werker & Lalonde, 1988). But there are many differences between the perceptual tuning of the sounds of oneÕs language and the conceptual tuning of semantic categories that result from what the language emphasizes.…”
Section: Discussionmentioning
confidence: 79%
“…In early childhood, native language environment starts to shape the perception of speech sounds (Kuhl et al, 1992;Kuhl et al, 2006;Ortiz-Mantilla et al, 2013), and improvements in speech perception accuracy are still seen during the first three grades . Further, longitudinal studies have found that the differences in speech perception ability between children with and without dyslexia vary depending on age , and suggestions have been made of different developmental trajectory of the perceptual abilities of children with language related difficulties Wright and Zecker, 2004).…”
Section: Atypical Quantity Perceptionmentioning
confidence: 99%
“…For example, in English, there is a difference in voice onset time between the two instances of /p/ in 'perceptual', but an English child will learn to ignore this difference, whereas she will learn not to ignore the meaningful difference between the voice onset times in the initial sounds in 'pear' and 'bear'. Despite the apparent difficulty of this learning task, infants have already learned their native phonetic contrasts before their first birthday (vowels by six months: Kuhl, Williams, Lacerda, Stevens, & Lindblom, 1992; consonants by ten months: Werker & Tees, 1984). It remains unclear, however, how infants start building such optimally restricted categories, that is, how they learn to focus on only those contrasts that are relevant for their native language (Werker & Tees, 1984).…”
Section: Introductionmentioning
confidence: 99%